Skrining Kejadian Self Harm pada Remaja di Palembang : Penelitian - Fathurohman; Riko Sandra Putra (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Self-harm is a behavior that can have a negative impact on adolescents' mental health and well-being. It is often carried out as a means of expressing emotions that are not properly processed or managed.. This research employs a quantitative method with a descriptive survey design and a cross-sectional approach. The instrument used is the Self-Harm Inventory (SHI). Data analysis was conducted univariately using SPSS. The screening results indicate that 61.1% of adolescents exhibit a moderate level of self-harm, 28.6% a high level, and 10.3% a low level. Based on these findings, early detection and intervention efforts are necessary to prevent the negative impacts of self-harm on adolescents.